Analisis Perpindahan Panas pada Pendingin CPU dengan Menggunakan Metode Elemen Hingga - Firmansyah Burlian (Jurnal Rekayasa Mesin, 2009)
Thermal management is an important part of the design process of most electronic devices. Thermal management is important both at the component level and system level plays an important role in device quality, efficiency, and, above all, itsreliability. One method of thermal management in electronic devices is the use of water-cooling block on the CPU. In this study conducted an analysis of heat transfer using CPU cooling Finite element method. Water analysis results showed that using the CPU block is longer fins transfer heat value better than the CPU water block using shorter fins, with a comparison of numerical and analytical calculation of temperature difference on each dimension of the fin surface obtained between 0.005% to 0.7 %.